Disease and mortality in sub-saharan Africa - Jamison, Dean T.; World Bank. (Washington, D.C. : World Bank, 2006)
Current data and trends in morbidity and mortality for the sub-Saharan Region as presented in this new edition reflect the heavy toll that HIV/AIDS has had on health indicators, leading to either a stalling or reversal of the gains made, not just for communicable disorders, but for cancers, as well as mental and neurological disorders.
Includes bibliographical references and index.
rpm 27/09/16
Loans
Keywords: Public health